Inhibition of HMG-CoA Reductase Activity from Date palm (Phoenix dactylifera L.) fruit's polyphenols: In-Silico Study - Aida Ayu Chandrawati; Marhaen Hardjo; Syahrijuita Kadir (Fakultas Kedokteran Universitas Muslim Indonesia, 2025)
Background: Hyperlipidemia is a group of conditions, both inherited and acquired, where there is too much fat in the body. While the condition itself often doesn't cause noticeable symptoms, it can lead to serious diseases that may be dangerous. HMG-CoA Reductase (HMGCR) is the enzyme that antihyperlipidemic medicines target. Recent studies suggest that eating diets based on date fruits may provide several health benefits, mainly because they are rich in plant-based polyphenols. Objective: This study looked at how polyphenols from date palms might stop HMG-CoA reductase from working. The polyphenols tested came from Phoenix dactylifera L. fruit and included gallic acid, catechin, rutin, quercetin, isoquercetin, kaempferol, ferulic acid, caffeic acid, cinnamic acid, syringic acid, and vanillic acid. Methods: The study used a computer-based method called molecular docking to predict how well these compounds could block the enzyme. Binding affinity scores were used to measure how strongly they could stop the enzyme. The process included preparing the chemicals and protein, running the docking simulation, and checking if the compounds were likely to be used as drugs. Results: The study found that date palm polyphenols could be useful in lowering lipids, with catechin showing the strongest effect, having a binding score of −8.5. Conclusion: Polyphenols in dates can act as natural agents to lower lipids by stopping the HMG-CoA reductase enzyme, making them a possible addition to treatments for high lipid levels.